Melanoma risk for CDKN2A mutation carriers who are relatives of population-based case carriers in Australia and the UK. Issue 4 (15th February 2011) - Cust, Anne E; Harland, Mark; Makalic, Enes; Schmidt, Daniel; Dowty, James G; Aitken, Joanne F; Agha-Hamilton, Chantelle; Armstrong, Bruce K; Barrett, Jenny H; Chan, May; Chang, Yu-Mei; Gascoyne, Joanne; et al.
Abstract : Background: CDKN2A mutations confer a substantial risk of cutaneous melanoma; however, the magnitude of risk is uncertain. Methods: The study estimated the hazard ratio (HR) and the average age specific cumulative risk (ie, penetrance) of reported melanoma for CDKN2A mutation carriers in case families using a modified segregation analysis of the first and higher degree relatives of 35 population-based cases. The study sample included 223 relatives of 13 melanoma cases diagnosed when aged 18–39 years from Melbourne, Sydney and Brisbane, Australia, and 322 relatives of 22 melanoma cases diagnosed at any age from Yorkshire, UK. Results: The estimated HR for melanoma for mutation carriers relative to the general population decreased with regions of increasing ambient ultraviolet (UV) irradiance, being higher for the UK than Australia (87, 95% CI 50 to 153 vs 31, 95% CI 20 to 50, p=0.008), and across Australia, 49 (95% CI 24 to 98) for Melbourne, 44 (95% CI 22 to 88) for Sydney, and 9 (95% CI 2 to 33) for Brisbane (p=0.02). Penetrance did not differ by geographic region. It is estimated that 16% (95% CI 10% to 27%) of UK and 20% (95% CI 13% to 30%) of Australian CDKN2A mutation carriers would be diagnosed with melanoma by age 50 years, and 45% (95% CI 29% to 65%) and 52% (95% CI 37% to 69%), respectively, by age 80 years. Conclusions: Contrary to the strong association between UV radiation exposure and melanoma risk for the general population, CDKN2A mutation carriers appear to have the same cumulative risk of melanoma irrespective of the ambient UV irradiance of the region in which they live.